HUBUNGAN STATUS PEGAWAI DENGAN KOMITMEN ORGANISASI, KEPUASAN KERJA, ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN KINERJA PADA PERAWAT PNS DAN KONTRAK DI RUMAH SAKIT MAYJEN H.A. THALIB KABUPATEN KERINCI - , ALPIANTRI, Dr. Mubasysyir Hasanbasri, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Hospital has the human resources consisting of government nurses and contract nurses. The differences in employment status between the two groups of nurses allows the high turnover, particularly on the contract staff nurses. The high turnover will adversely affect the stability and continuity of nursing care related to organizational commitment, job satisfaction, organizational citizenship behavior and performance. Objective: This study aimed to determine the differences between civil servants nurses and contract nurses in organizational commitment, job satisfaction, organizational citizenship behavior and performance. Methods: This research was quantitative study with cross-sectional design. Subjects were all civil servant nurses and contract nurses (total population, n=157 ). Data was collected with structured questionnaire. Data analysis was performed using chi-square to determine the difference between civil nurses and contract nurses in organizational commitment, job satisfaction and organizational citizenship behavior and performance. Results: Organizational commitment, job satisfaction, organizational citizenship behavior and performance, government staff had been mostly higher as compared to contract nurses. Significant differences for organizational commitment was on sub variable affective commitment with p-value <0.05, job satisfaction subvariables of consisting salary and promotion opportunities with p-value <0.05, organizational citizenship behavior with sub variables of altruism with p-value <0.05 and the performance of sub variable quality of the work with p-value <0.05. Conclusion: Civil servant nurses have organizational commitment, job satisfaction, OCB and performance higher than the contract nurses, because of the guarantee of compensation and a higher salary as well as a clear in career development compared to contract nurses. It is a need to have written commitment to contract, and efforts to improve of the management fair compensation system and a better salary.